Distribusi Jenis Kelelawar (Pteropodidae) Pada Berbagai Tipe Penutupanan Lahan di Sekitar Kawasan Taman Nasional Kerinci Seblat (TNKS) - Nugroho, Pandam; Sukandar, Paskal (Perhimpunan Biologi Indonesia, 2008)
ABSTRACTThe Mega Bat (Pteropodidae) Distribution on Several Land Coverage at Surrounding KerinciNational Park. The study of bats was carried out on May 2005 to July 2005. In all 5 major landuse system (primary forest, disturbed forest, old rubber plantation, young rubber plantationand mix garden) survey was conducted using the same standardized mistnetting. Each of theland use system was sampled for 4 days using 4 mist-nets a night. The total of 2512.5 m2 ofmist-nets night area were set during this survey. A total of 156 bat individuals which consist of14 specieses and 5 families (Pteropodidae, Vespertilonidae, Emballonuridae, Hipposideridaeand Rhinolophidae) acquired. Calculation result using the diversity index measurement frombat samples indicate that the highest diversity was in disturbed forest habitat (Hâ=1.831;E=0,865) and the lowest was in forest habitat (Hâ=0.5; E=0.561), meanwhile the biggestdominancy reside in the young rubber plantation (?=0.767) and disturbed forest had the lowestdominancy (?=0,138). The most dominant at young rubber plantation habitat is Cynopterusbrachyotis. The result of clustering analysis using SPSS 11.5 showed that habitat type weredivided become 2 clusters which were old rubber and non old forest (forest, disturbed forest,young rubber plantation and mix garden). This division showed that forest and non forest hada distinctively different habitat. According to Canonical Correspondence Analysis (CCA) byusing Canoco for Windows version 4.5 indicated that physical parameter such as temperature,humidity, rainfall and altitude influenced the distribution, commnunity and clustering of batsfor land use systemKey words: Bats, diversity, Kerinci Seblat National Park, land use type, rubber plantation